SHP-2-induced M2 polarization of tumor associated macrophages via IL-4 regulate colorectal cancer progression - Li, Zhihan; Xi, Jinchuan; Li, Baokun; Liu, Youqiang; Wang, Guiying; Yu, Bin; Ma, Hongqing; Li, Zhilin; Zhang, Zhenya (Frontiers in Oncology, 2023)
Abstract Objective: To explore the effect and molecular mechanism of Src homology region 2 domain-containing protein tyrosine phosphatase-2 (SHP-2) in tumor-associated macrophages (TAMs) repressing the migration and invasion of colorectal cancer (CRC) cells. Methods: The relevant data sets of human colon specimens were obtained from GEO database, and then the performed correlation analysis, principal component analysis and differentially expressed gene (DEGs) analysis on the samples were conducted. GO and KEGG enrichment analysis were performed on the common DEGs, and then functional interaction prediction was performed to verify the gene regulatory circuit of SHP-2. Furthermore, western blot was used to detect the effect of low expression of SHP-2 on related proteins, including the markers of promoting M2 polarization and exosome secretion, and keys proteins of the PI3K pathway. The relationship between SHP-2 and PI3K pathway was further verified by adding PI3K inhibitor LY294002. Finally, the effect of SHP-2 on the function of colon cancer cells was confirmed by wound healing assay and Transwell assay. Results: Through bioinformatics analysis, SHP-2 was screened as a possible key gene affecting CRC. The low expression of SHP-2 promoted the protein levels of Arginase-1 and IL-10 in IL-4 induced M2 macrophages, while inhibited the protein levels of IL-1β and TNF-α. Meanwhile, low expression of SHP-2 was found to similarly promote the expression of p-PI3K, p-AKT, and the release of exosomes. Interestingly, the promotion was suppressed after the addition of the PI3K inhibitor LY294002. In terms of cellular behavior, wound healing and transwell data showed that low expression of SHP-2 enhanced the migration and invasion abilities of CRC cells. Conclusion: The low expression of SHP-2 induced by PHPS1 may regulate M2 polarization of TAMs and release of exosomes through PI3K/AKT pathway, thereby enhancing the migration and invasion ability of CRC cells. Keywords: Src homology region 2 domain-containing protein tyrosine phosphatase-2; Tumor-associated macrophages; Colorectal cancer; Migration, Invasion